Representation as power and performative practice: Global civil society advocacy for working children - Anna Holzscheiter (Review of international studies, 2016)
This article analyses global civil society advocacy in the field of child labour through the lens of theories on political representation in global governance. The article is sympathetic to newer theories on political representation which, fundamentally, understand representation as a dialectic of performative practices between representatives and their real or imagined constituencies. However, the article argues that the contemporary literature on political representation turns a blind eye on two aspects that are central to understanding this dialectic of representation in the child labour case: first, representation as power and second, the contested nature of citizenship. The article thus proposes an approach to political representation that allows highlighting the power-dimension inherent to the interrelation between formal and performative aspects of representation, that is, between civil society actors' power to represent and their power over representation. Using such an approach, the article presents empirical insights on CSO representation in global policymaking on child labour – a field in which conflicts over legitimate representation, citizenship, and grassroots participation continue to be exceptionally fierce.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; civil society; non-governmental organization; child labor; representation; global governance; political theory; power